Freud and religion advancing the dialogue - Parsons, William 1976- (Cambridge University Press, 2021)
We live in an era that often described as 'therapeutic.' Our culture is suffused with unconscious fantasies and psychoanalytic ways of thinking about self, other, and society. Aspects of the Freudian cultural universe have also had an impact on how we think about religion. In this volume, William Parsons explores the relationship between religion and psychoanalysis through multiple, linked investigations. Why did Freud write about religion and what did he say? What were the multiple critiques levelled at his work? What were the post-Freudian psychoanalytic advances? How can we still apply psychoanalytic ideas going forward? In answering these and related questions, Parsons distinguishes between classic-reductive, adaptive, and transformational psychoanalytic models. He also argues that the psychoanalytic theory of religion needs to integrate reflexive, dialogical, and inclusive elements as part of its toolkit. Offering illustrations and applications of such revisions, Parsons creates new capacities for thinking psychologically and critically about religion
Title from publisher's bibliographic system (viewed on 07 May 2021)
Keywords: Freud, Sigmund / 1856-1939 / Religion; Psychoanalysis and religion